Acute toxicity, secondary metabolites, and antioxidant activity of Macaranga tanarius from post-coal mining and non-mining areas in East Kalimantan, Indonesia - Fikriah, Ika; Masruhin, Muhammad A.; Paramita, Swandari; Marliana, Eva; Panggabean, Aman S.; Ismail, Sjarif; Kusuma, Irawan W.; Kim, Yong-ung; Kim, Soo-Ya (Narra J, 2024)
Coal plays a crucial role in Indonesia’s foreign exchange and East Kalimantan’s revenue sharing, yet its environmental impacts, including soil acidification, raises concerns. Reclamation measures involve revegetation with pioneer plants such as Macaranga sp., known for their medicinal properties. However, the pharmacological properties of these plants are influenced by secondary metabolites, which depend on soil parameters such as pH and nutrient levels. The aim of this study was to evaluate the acute toxicity, secondary metabolites, and antioxidant activities of Macaranga tanarius leaf extracts from post-coal mining area (MTPCMA) and non-mining area (MTNMA) alongside soil parameters. Acute toxicity of M. tanarius leaf extracts and soils were assessed using the brine shrimp lethality test (BSLT). Phytochemical screening was done using thin-layer chromatography (TLC), determining total phenolic (TPC) and flavonoid content (TFC). The DPPH radical scavenging assay was used to assess the antioxidant activity. A comparative analysis between MTPCMA and MTNMA was conducted using Student t-test. The data showed no significant difference in toxicity between MTPCMA and MTNMA leaf extracts (LC50 of 100–1000 µg/mL) (p=0.062), and soils from both areas were non-toxic (LC50 of >1000 µg/mL). Although heavy metal concentrations were higher in PCMA than in NMA soil (p<0.001), secondary metabolite compounds and TFC in both extracts were not significantly different (p=0.076). Both extracts contained flavonoids and polyphenols with antioxidant activity and terpenoids without antioxidant activities. The DPPH radical scavenging test suggested insignificant antioxidant activity between MTPCMA and MTNMA extracts (p=0.237). In conclusion, non-toxic soils in post-mining land and insignificant differences between MTPCMA and MTNMA extracts suggest good soil nutrient availability, highlighting the success of land recovery after 10 years of revegetation with M. tanarius.